The Effect Of Implementation Point, Illustration, And Explanation Toward Student’s Motivation In Writing Skill - I Made Permadi Utama; Tri Setianingsih (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2019)
This research aimed to find out the effect of implementation Point, Illustration, and Explanation towards students’ motivation in writing skill for first grade of MA Darunnajah Al-Falah in academic year 2019/2020 whether there is any possitive effect or not. The method of this research was experimental research (pre-experimental pre-test post-test design). The population of this research was all of the first grade students o MA Darunnajah Al- Falah which is consisted of one class. The samples were all population. Students had the test before treated by using Point, Illustration, and Explanation strategy and the instrument used essay test and questionnaire. The result of the research showed that, there was significant effect of Point, Illustration, and Explanation towards students’ motivation in writing. The result of the data analysis showed that t-test was 4.684 and the result of t-table was 1.703 in significance level 0.05.It meant that the score of t-test was higher than t-table (4,684 > 1.703 ). Therefore, Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. From the result of data analysis above, the researcher concluded that through the implementation of PIE there is possitive effect towards students’ motivation in writing skill in the first grade students of MA Darunnajah in academic year 2019/2020.